The environmental effects of regional economic cooperation: Evidence from the Belt and Road Initiative - Li, Baoxi; Hu, Jiemei; Chen, Guo; Xiao, De; Cheng, Shixiong (Frontiers in Environmental Science, 2022)
China’s Belt and Road Initiative is a significant regional economic cooperation. This paper uses the Belt and Road Initiative (BRI) as a quasi-natural experiment to investigate the impact of regional economic cooperation on environmental quality. Using difference-in-differences (DID) and a series of robustness checks, we find that, on average regional economic cooperation like BRI has a negative effect on environmental quality in countries along the Belt and Road. The main reason is that the improving effects on environmental quality in the BRI countries are smaller than in the non-BRI countries after the BRI. The environmental impacts of the BRI exist differences in different countries. The results show that the BRI improves environmental quality in South Asia and Europe & Central Asia regions. However, the BRI negatively affects environmental quality in East Asia & Pacific region, developing countries, and non-OECD countries. We found that, different from the BRI, the Green BRI improves environmental quality in countries along the Belt and Road. Additionally, we also discuss the mechanism of the BRI on environmental quality from foreign direct investment (FDI).